Mohs micrographic surgery for basal cell carcinoma: evaluation of the indication criteria and predictive factors for extensive subclinical spread. (1st April 2016) - Hoorens, I.; Batteauw, A.; Van Maele, G.; Lapiere, K.; Boone, B.; Ongenae, K.
Summary: Background: The incidence of basal cell carcinoma (BCC) is rising and BCC treatment has an important impact on healthcare budget. Mohs micrographic surgery (MMS) has the highest 5‐year cure rate but is an expensive technique. Objectives: To study the indication criteria for MMS, using a series of 1062 patients treated for facial BCCs between 1998 and 2011. Methods: The accuracy of the indication criteria was evaluated by comparing the characteristics of BCC requiring one vs. more than one round of MMS. Predictors for extensive subclinical spread (three or more rounds) were examined using the preoperative patient and all tumour characteristics. Results: BCCs with a surface > 1 cm 2 and aggressive histology (morphoeaform and micronodular), and a patient age > 80 years are strong predictors for two or more rounds of MMS being required. Extensive subclinical spread was present in recurrent tumours, morphoeaform BCC or BCC with mixed histology. Conclusions: We found that tumour size and aggressive histology are the strongest indication criteria for MMS. Recurrence and aggressive histology are predictors for extensive subclinical spread but not for two or more rounds of MMS. Evidence‐based indications for MMS are necessary to ensure cost‐effective management of BCC.